The symbolic Afro-Mexican identity through its cuisine: An approach to its cultural heritage - González Rodríguez, Guillermo Isaac (2023)
Within the formation of cultural symbolic heritage, gastronomy plays a fundamental role as it serves as the meeting point between the identity and historical roots of a community, people, or race, generating a distinctive-representative blend of their origin, worldview, and cosmology. Therefore, this present study aims to describe the culture, traditions, and symbols that exist within the Afro-Mexican communities in the Cuajinicuilapa region, Mexico. Through a descriptive diagnosis, their main festive elements are presented as part of their culture, along with the gastronomy that accompanies symbolic and ritual processes. A qualitative methodology is employed, using a descriptive-sequential method and two applied instruments. The study concludes by obtaining an inventory of traditions that Afro-Mexican individuals preserve as part of their cultural history and replicate as a symbol of their identity.